Polymer nanofiber material, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202510509859.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
然而以上的这些方法有各自缺点,静电纺丝存在产量低、有机溶剂污染问题;模板法存在过程复杂,产量低的问题;自组装存在耗时长的问题;水热碳化法和化学气相沉积法存在条件苛刻和产量低的问题
[0037]本发明基于聚合物颗粒与溶剂二者表面能的关系,尤其是聚合物与溶剂表面能之间差值的绝对值≤50mJ·m-2,筛选得到一种聚合物溶液,该聚合物溶液在微通道的高流速下(同时满足U*η/丨A-B丨≥1),聚合物能够被流体流动充分带动,进而被拉伸成纳米纤维,反之无法形成。本发明提出了一种聚合物纳米纤维化的方法,可使难以加工的聚合物(例如:超高分子量聚乙烯、聚醚醚酮、聚酰亚胺等)在绿色溶剂中进行纳米纤维化,并可后续易加工成型。
Smart Images

Figure CN122959873A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiber materials technology, and in particular to a polymer nanofiber material, its preparation method, and its application. Background Technology
[0002] With the rapid development of nanotechnology, nanomaterials and nanofibers have become important tools for solving many scientific and engineering problems. Polymer nanofibers possess the characteristics of polymers while also exhibiting the characteristics of nanofibers. They have attracted widespread attention due to their high specific surface area, high porosity, excellent mechanical properties, and multifunctionality. Nanofiber research began in the late 20th century and has expanded rapidly with the development of preparation technologies such as electrospinning. Especially in the 21st century, the global demand for new materials (such as high-efficiency separation and filtration, biomedical materials, battery separators, catalyst supports, and functional fabrics) has driven the research and application of polymer nanofibers. Current methods for preparing polymer nanofibers include electrospinning, self-assembly, template methods, hydrothermal carbonization, and chemical vapor deposition. However, each of these methods has its own drawbacks: electrospinning suffers from low yield and organic solvent pollution; template methods are complex and have low yields; self-assembly is time-consuming; and hydrothermal carbonization and chemical vapor deposition are subject to harsh conditions and low yields. Summary of the Invention
[0003] To address the aforementioned technical problems, this invention provides a general-purpose, high-yield, and environmentally friendly polymer nanofiber material and its preparation method, which is prepared by screening polymer dispersions based on the relationship between the surface energies of polymer particles and solvents.
[0004] The technical solution of the present invention is as follows:
[0005] A polymer dispersion comprising a polymer and a dispersion solvent.
[0006] According to an embodiment of the present invention, the polymer is in particulate form.
[0007] According to an embodiment of the present invention, the polymer is selected from linear polymers, including at least one of nylon, polyethylene, polypropylene, polystyrene, polyimide, polyetheretherketone, and polytetrafluoroethylene.
[0008] According to an embodiment of the present invention, the dispersing solvent includes at least one or more of water, ethanol, isopropanol, glycerol, and silicone oil.
[0009] According to an embodiment of the present invention, the absolute value of the difference between the surface energy A of the polymer and the surface energy B of the dispersing solvent has the following relationship: |AB| ≤ 50 mJ·m -2 The absolute value of the difference is, for example, 40 mJ·m -2, 30mJ·m -2 , 20mJ·m -2 , 10mJ·m -2 , 5mJ·m -2 , 1mJ·m -2 .
[0010] According to an embodiment of the present invention, in the polymer dispersion, the concentration of the polymer is 0.01g / L to 100g / L, for example 0.1g / L, 1g / L, 10g / L.
[0011] According to an embodiment of the present invention, the polymer dispersion is obtained by dispersing a polymer in a dispersion solvent.
[0012] The present invention further provides a method for preparing a polymer nanofiber material, which comprises: subjecting the above-mentioned polymer dispersion to polymer stretching in a microchannel to obtain the polymer nanofiber material.
[0013] According to an embodiment of the present invention, the microchannel may adopt equipment known in the art, for example, at least one of a high-pressure microfluidizer device, a microfluidic device, and a self-made microchannel processing device.
[0014] According to an embodiment of the present invention, the diameter of the microchannel is 10 micrometers to 1000 micrometers, for example 100 micrometers, 500 micrometers.
[0015] According to an embodiment of the present invention, the working pressure in the microchannel is 5MPa to 500MPa, for example 10MPa, 100MPa.
[0016] According to an embodiment of the present invention, the flow rate U of the polymer dispersion in the microchannel is 10m / s to 10000m / s, for example 100m / s, 1000m / s.
[0017] According to an embodiment of the present invention, the flow rate U of the polymer dispersion in the microchannel and the polymer dispersion further satisfy the following relationship:
[0018] U*η / |A-B|≥1,
[0019] Wherein, U refers to the flow rate of the polymer dispersion, η refers to the viscosity of the dispersion solvent, and |A-B| has the definition as described above.
[0020] According to an embodiment of the present invention, the polymer dispersion in the microchannel can be circulated multiple times in the microchannel. Preferably, the number of cycles is at least 5 times, for example 10 times, 20 times, 100 times.
[0021] The present invention further provides a polymer nanofiber material, which is obtained by the above-mentioned preparation method.
[0022] According to an embodiment of the present invention, the diameter of the polymer nanofiber material is no greater than 10 micrometers.
[0023] The present invention also provides applications of the above-mentioned polymer nanofiber materials, such as in high thermal conductivity materials, battery separators, separation membranes, biomedical materials, catalyst supports, functional fabrics or other polymers.
[0024] According to an embodiment of the present invention, the high thermal conductivity material is, for example, a thermally conductive pad.
[0025] According to an embodiment of the present invention, the battery separator or separation membrane is, for example, a porous membrane.
[0026] The present invention also provides a thermally conductive pad comprising the above-mentioned polymer nanofiber material.
[0027] According to an embodiment of the present invention, the thickness of the thermal pad is greater than 1 μm, for example, 23 μm.
[0028] According to an embodiment of the present invention, the thermal conductivity of the thermal pad is not less than 2 W / mK, for example, 2.53 W / mK or 2.86 W / mK.
[0029] According to an embodiment of the present invention, the thermal resistance of the thermally conductive pad is not greater than 1×10⁻⁶. -5 Km 2 / W, for example, 0.909×10 -5 Km 2 / W, 0.809×10 -5 Km 2 / W.
[0030] According to an embodiment of the present invention, the thermally conductive pad is prepared, for example, by heating a dispersion of the polymer nanofiber material to remove the solvent, thereby obtaining the thermally conductive pad. Preferably, the heating conditions are: 30-100°C, 2-6 hours.
[0031] According to an embodiment of the present invention, the solvent in the dispersion of the polymer nanofiber material may be a solvent known in the art, such as one selected from the above-mentioned dispersion solvents.
[0032] The present invention also provides a porous membrane comprising the above-mentioned polymer nanofiber material.
[0033] According to the embodiments of the present invention, the porous membrane has a rejection rate for inorganic substances of not less than 50%. Preferably, the porous membrane has a rejection rate for sodium sulfate of not less than 97%. Preferably, the porous membrane has a rejection rate for magnesium sulfate of not less than 96%. Preferably, the porous membrane has a rejection rate for magnesium chloride of not less than 85%. Preferably, the porous membrane has a rejection rate for sodium chloride of not less than 51%. Preferably, the porous membrane has a rejection rate for lithium chloride of not less than 61%.
[0034] According to the embodiments of the present invention, the porous membrane is prepared, for example, by the following method: the dispersion of the polymer nanofiber material is subjected to spray coating or suction filtration, so as to obtain the porous membrane.
[0035] According to the embodiments of the present invention, the solvent in the dispersion of the polymer nanofiber material may be a solvent known in the art, for example, selected from the aforementioned dispersion solvents.
[0036] Beneficial effects:
[0037] The present invention is based on the relationship between the surface energies of polymer particles and solvents, especially the absolute value of the difference between the surface energies of the polymer and the solvent is ≤ 50 mJ·m -2 , a polymer solution is screened out. Under the high flow rate of the microchannel (while satisfying U*η / |A-B| ≥ 1), the polymer can be fully driven by the fluid flow and then stretched into nanofibers; otherwise, it cannot be formed. The present invention proposes a method for polymer nanofibrillation, which enables polymers that are difficult to process (for example: ultra-high molecular weight polyethylene, polyether ether ketone, polyimide, etc.) to undergo nanofibrillation in green solvents, and can be easily processed and shaped in subsequent steps.
[0038] The polymer nanofiber material prepared by the present invention has the characteristics of high specific surface area and oriented stretched arrangement of the polymer, and the polymer nanofibers have high thermal conductivity. The dispersion of the polymer nanofiber material of the present invention can be used as an ink directly for polymer molding processing, and can be directly shaped by heating deposition, spray coating, suction filtration, and freeze drying. The polymer nanofiber material prepared by the present invention has good application prospects in separation, battery separators, thermal conduction, biomedical materials, catalyst carriers, functional fabrics or other polymer-related applications. Brief Description of the Drawings
[0039] Figure 1 It is a scanning electron microscope image of the polymer nanofiber material of Example 1 and the comparative polymer nanofiber materials of Comparative Examples 1-2.
[0040] Figure 2 It is a scanning electron microscope image of the polymer nanofiber material of Example 2.
[0041] Figure 3is a scanning electron microscope image of the polymer nanofiber material of Example 3.
[0042] Figure 4 is a schematic diagram of the batch preparation of PA-12 nanofiber dispersion. DETAILED DESCRIPTION OF EMBODIMENTS
[0043] The technical solution of the present invention will be further described in detail below with reference to specific examples. It should be understood that the following examples are only for exemplarily illustrating and explaining the present invention, and shall not be construed as limiting the protection scope of the present invention. All technologies implemented based on the above content of the present invention are covered within the intended protection scope of the present invention.
[0044] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods.
[0045] The following examples are intended to illustrate the present invention, but not to limit the scope of the present invention.
[0046] Example 1
[0047] The preparation method of the polymer nanofiber material in this example includes the following steps:
[0048] (1) Polytetrafluoroethylene powder particles are dispersed in isopropanol to obtain a polytetrafluoroethylene isopropanol dispersion with a concentration of 1g / L. The polytetrafluoroethylene particles are purchased from Nanjing Tianshi PTFE-0154; the surface energy of polytetrafluoroethylene is 18mJ·m -2 , and the surface energy of isopropanol is 21.7mJ·m -2 , and the absolute value of the difference between the two is 3.7 ≤ 50mJ·m -2 .
[0049] (2) The polytetrafluoroethylene isopropanol dispersion is placed in a high-pressure microfluidizer to stretch the polytetrafluoroethylene particles. The working pressure is 100MPa, the microchannel diameter is 100 micrometers, the flow rate is controlled at 350m / s, the viscosity η of isopropanol at 25°C is 0.0024Pa·s, U*η / |A-B|=280 ≥ 1. The mixture is circulated 100 times in the microchannel, and finally the ethanol dispersion of polytetrafluoroethylene nanofiber material is obtained.
[0050] Comparative Example 1
[0051] A polymer nanofiber comparative material is prepared by referring to the method of Example 1, with the difference that:
[0052] The isopropanol in step (1) is replaced with water, that is, the surface energy of polytetrafluoroethylene is 18mJ·m -2 , the surface energy of water is 72mJ·m -2 , and the absolute value of the difference between the two is 54 > 50mJ·m-2 , obtaining an aqueous polytetrafluoroethylene dispersion;
[0053] The operating conditions in step (2) are the same as those in Example 1, except that the isopropanol dispersion of polytetrafluoroethylene is replaced with the aqueous polytetrafluoroethylene dispersion of this Comparative Example, and the same treatment is performed to obtain Polymer Nanfiber Comparative Material 1. The viscosity η of water at 25°C is 0.001 Pa·s, and U*η / |A-B|=6.48≥1
[0054] Comparative Example 2
[0055] A polymer nanofiber comparative material was prepared by referring to the method of Example 1, with the differences as follows:
[0056] The flow rate in step (2) is 50 m / s, the viscosity η of isopropanol at 25°C is 0.0024 Pa·s, and U*η / |A-B|=0.92<1, to obtain Polymer Nanofiber Comparative Material 2.
[0057] Test Example 1
[0058] The polymer nanofiber material of Example 1 and the polymer nanofiber comparative materials of Comparative Example 1 were respectively taken as samples, and the scanning electron microscopy results are shown in Figure 1 , where, Figure 1 (A) in the figure is polytetrafluoroethylene powder particles, Figure 1 (B) in the figure is polytetrafluoroethylene nanofibers, Figure 1 (C) in the figure is the polytetrafluoroethylene treated in Comparative Example 1, Figure 1 (D) in the figure is the polytetrafluoroethylene treated in Comparative Example 2.
[0059] Example 2
[0060] The preparation method of the polymer nanofiber material and the nylon-12 gasket in this example is as follows:
[0061] (1) Nylon-12 powder particles are dispersed in water to obtain an aqueous nylon-12 dispersion with a concentration of 1 g / L. The nylon particles are purchased from Evonik, Germany as PA12 powder VESTOSINT 1164; the surface energy of nylon-12 is 34.8 mJ·m -2 , the surface energy of water is 72 mJ·m -2 , and the absolute value of the difference between the two is 37.8 ≤ 50 mJ·m -2 .
[0062] (2) The aqueous dispersion of nylon-12 is placed in a high-pressure microfluidizer to stretch the nylon-12 particles, with a working pressure of 100 MPa, a microchannel diameter of 100 micrometers, a flow rate controlled at 350 m / s, the viscosity η of water at 25°C is 0.001 Pa·s, U*η / |A-B|=9.4≥1, and 100 cycles are performed in the microchannel. Finally, an aqueous dispersion of nylon-12 nanofiber material is obtained;
[0063] (3) The obtained aqueous dispersion of nylon-12 nanofiber material is subjected to heating deposition, 50 mL is taken and placed in a 25.4 cm*25.4 cm mold, the solvent is removed at 60°C for 3 h, and finally the nylon-12 gasket is obtained.
[0064] Comparative Example 2
[0065] The preparation method of the nylon-12 gasket comparative sample prepared in this comparative example is as follows:
[0066] The nylon-12 powder particles in step (1) of Example 2 are directly placed into a 25.4 cm*25.4 cm mold for heating deposition, and the specific deposition conditions are: diameter hot pressing at 20 MPa, 180°C for 3 h, to obtain a nylon-12 gasket comparative sample with the same mass and area as Example 2.
[0067] Test Example 2-1
[0068] The nylon-12 powder particles in step (1) of Example 2 and the nylon-12 nanofiber material in step (2) are respectively taken as samples, and their scanning electron microscopy results are shown in Figure 2 as shown, Figure 2 the right figure in is the nylon-12 nanofiber material, Figure 2 the left figure in is the unprocessed nylon-12 powder particles.
[0069] Test Example 2-2
[0070] The nylon-12 gasket in step (3) of Example 2 and the nylon-12 gasket comparative sample in Comparative Example 2 are respectively taken to test the thermal conductivity, the test standard is ASTM D5470, the test equipment is longwin (Taiwan) lw 9389, the thermal resistance and thickness are obtained through testing, the thermal conductivity is equal to thickness / thermal resistance, and the test results are shown in Table 1.
[0071] Test Example 2-3
[0072] The aqueous dispersion of the nylon-12 nanofiber material obtained in step (2) of Example 2 is sprayed onto a nylon filter membrane with a pore size of 100 nanometers, and the solvent volatilizes rapidly to form a nylon-12 porous membrane. The membrane separation performance of this nylon-12 porous membrane is tested. The test equipment is SF-SA from Hangzhou Saifei Membrane Separation Technology Co., Ltd., the test pressure is 1 bar, and the test solutions are sodium sulfate, magnesium sulfate, magnesium chloride, sodium chloride, and lithium chloride solutions with a concentration of 1 g / L. The concentrations of the feed solution and the filtrate are measured by Leici DDB-303. The rejection rate = (1 - concentration of filtrate / concentration of feed solution) * 100%, and the test results are shown in Table 2.
[0073] Example 3
[0074] The preparation method of the polymer nanofiber material and its gasket in this example is as follows:
[0075] (1) Disperse polyethylene powder particles in ethanol to obtain an ethanol dispersion of polyethylene with a concentration of 1 g / L. The polyethylene particles are 800-mesh ultra-fine powder of ultra-high molecular weight polyethylene from Korea Oil Chemical; the surface energy of polyethylene is 31 mJ·m -2 , and the surface energy of ethanol is 22.39 mJ·m -2 , the absolute value of the difference between the two is 8.61 ≤ 50 mJ·m -2 .
[0076] (2) Put the ethanol dispersion of polyethylene into a microfluidic device to stretch the polyethylene particles. The working pressure is 100 MPa, the diameter of the microchannel is 100 micrometers, the flow rate is controlled at 350 m / s, the viscosity η of ethanol at 25°C is 0.00107 Pa·s, U*η / |A-B| = 43.5 ≥ 1, and 100 cycles are performed in the microchannel. Finally, an ethanol dispersion of polyethylene nanofiber material is obtained;
[0077] (3) Heat and deposit the obtained ethanol dispersion of polyethylene nanofiber material, take 50 mL and place it in a 25.4 cm*25.4 cm mold, remove the solvent at 60°C for 3 hours, and finally obtain a polyethylene gasket.
[0078] Comparative Example 3
[0079] The preparation method of the polyethylene gasket comparative sample prepared in this comparative example is as follows:
[0080] The polyethylene powder particles in step (1) of Example 3 are directly placed into a 25.4 cm*25.4 cm mold for heating deposition. The specific deposition conditions are: hot pressing at 150°C for 3 hours to obtain a polyethylene gasket comparative sample with the same mass and area as Example 3.
[0081] Test Example 3-1
[0082] The polyethylene powder particles from step (1) and the polyethylene nanofiber material from step (2) of Example 3 were taken as samples, and their scanning electron microscopy results are as follows: Figure 3 As shown, Figure 3 The right image shows polyethylene nanofiber material. Figure 3 The image in the middle left is a scanning electron microscope image of unprocessed polytetrafluoroethylene powder particles.
[0083] Test Example 3-2
[0084] 2) Take the polyethylene gasket from step (3) of Example 3 and the polyethylene gasket from Comparative Example 3 respectively to test the thermal conductivity. The test standard is ASTM D5470 and the test equipment is Longwin (Taiwan) LW 9389. The thermal resistance and thickness are obtained through the test. The thermal conductivity is equal to the thickness / thermal resistance. The test results are shown in Table 1.
[0085] Test Example 3-3
[0086] The ethanol dispersion of polyethylene nanofiber material obtained in step (2) of Example 3 was sprayed onto a nylon filter membrane with a pore size of 100 nanometers. The solvent evaporated rapidly to form a polyethylene porous membrane. The membrane separation performance of the polyethylene porous membrane was tested. The testing equipment was SF-SA from Hangzhou Saifei Membrane Separation Technology Co., Ltd., the test pressure was 1 bar, and the test solution was a solution of sodium sulfate, magnesium sulfate, magnesium chloride, sodium chloride, and lithium chloride with a concentration of 1 g / L. The concentration of the filtrate and the filtrate was tested using a Leici DDB-303. The rejection rate was calculated as (1 - filtrate concentration / filtrate concentration) * 100%. The test results are shown in Table 2.
[0087] The results are shown in Tables 1 and 2 below.
[0088] Table 1. Thermal conductivity test results
[0089]
[0090] Table 2 Retention rate (%) of different test solutions: Test results
[0091]
[0092] from Figure 1 , Figure 2 , Figure 3 It is evident that the method of this invention can prepare polymer nanofiber materials, but when the surface energy difference between the polymer and the solvent exceeds the screening range of this invention, polymer nanofibers cannot be prepared normally (e.g., Comparative Example 1, see Comparative Example 1). Figure 1 (As shown in the middle image), the polymer particles may break.
[0093] As shown in Table 1, when preparing polymer nanofiber materials using the method of this invention, the polymer can be stretched and oriented, resulting in a significant increase in the thermal conductivity of the polymer by more than 10 times. Table 2 shows that the polymer porous membrane prepared using the method of this invention can effectively separate and retain different inorganic salts in aqueous solutions. This invention can rapidly prepare polymer nanofiber materials with higher thermal conductivity, and the polymer nanofiber materials of this invention have promising application prospects.
[0094] from Figure 4 It can be seen that the method of the present invention can prepare polymer nanofiber materials in batches.
[0095] The exemplary embodiments of the present invention have been described above. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing polymer nanofiber materials, characterized in that, The preparation method comprises: subjecting a polymer dispersion to polymer stretching in a microchannel to obtain the polymer nanofiber material; The polymer dispersion comprises a polymer and a dispersion solvent; the absolute value of the difference between the surface energy A of the polymer and the surface energy B of the dispersion solvent has the following relationship: |AB| ≤ 50 mJ·m -2 .
2. The preparation method according to claim 1, characterized in that, The polymer is in a granular form; The polymer is selected from linear polymers, comprising at least one of nylon, polyethylene, polypropylene, polystyrene, polyimide, polyether ether ketone, and polytetrafluoroethylene.
3. The preparation method according to claim 1 or 2, characterized in that, The dispersion solvent comprises at least one or more of water, ethanol, isopropanol, glycerol, and silicone oil; In the polymer dispersion, the concentration of the polymer is 0.01 g / L to 100 g / L; The polymer dispersion is obtained by dispersing the polymer in a dispersion solvent.
4. The preparation method according to any one of claims 1-3, characterized in that, The diameter of the microchannel is 10 micrometers to 1000 micrometers; The working pressure in the microchannel is 5 MPa to 500 MPa; The flow rate U of the polymer dispersion in the microchannel is 10 m / s to 10000 m / s.
5. The preparation method according to any one of claims 1-4, characterized in that, The flow rate U of the polymer dispersion in the microchannel and the polymer dispersion further satisfy the following relationship: U*η / |A-B|≥1, Wherein, U refers to the flow rate of the polymer dispersion, η refers to the viscosity of the dispersion solvent, and |A-B| has the definition as described in Claim 1.
6. The preparation method according to any one of claims 1-5, characterized in that, The polymer dispersion in the microchannel is subjected to multiple cycles in the microchannel.
7. A polymer nanofiber material, which is obtained by the preparation method according to any one of Claims 1 to 6; The diameter of the polymer nanofiber material is not more than 10 micrometers.
8. Use of the polymer nanofiber material of Claim 7 in high thermal conductivity materials, battery separators, separation membranes, biomedical materials, catalyst supports, and functional fabrics.
9. A thermal conductive gasket, which comprises the polymer nanofiber material of Claim 7.
10. A porous membrane, characterized in that, The porous membrane comprises the polymer nanofiber material as described in Claim 7; The retention rate of the porous membrane for inorganic substances is not less than 50%.